Toxicity potential of electroplating wastewater and its bioremediation approaches: a review. Issue 1 (1st January 2021) - Kumar, Vinay; Dwivedi, S. K.
ABSTRACT: Electroplating industries produce a large amount of wastewater laden with a high amount of heavy metals and other toxic inorganic and organic contaminants. The wastewater generated from the process is highly toxic to all forms of life. It has severe toxicity to aquatic plants, fish and other living multicellular or unicellular organisms. On land, it affects germination rates, growth and development of plants and also causes heavy metal accumulation in vegetable and grain crops. Several human health issues are also associated with electroplating wastewater (EWW) due to its content of toxic metals and organic pollutants. The treatment of EWW is therefore essential before its disposal to protect the environment and its living organisms. This review identified the hazardous content of EWW and their toxicity The reviewed focused in particular on current bioremediation strategies for the safe treatment of EWW, their major challenges and future potential application. The review highlighted that integrated biological-treatment systems, such as constructed wetland can provide a cheap, eco-friendly and sustainable alternative to conventional technologies for the treatment of EWW. GRAPHICAL ABSTRACT: UF0001